Insight learning from the results of isc2 pile prediction event in residual soil - António Viana da Fonseca (2009)
In the north-western region of Portugal residual soils from granite are dominant, with specific and complex characteristics, typical of "non-textbooks" materials. Current design practice of bored and driven piles in residual weathered formations is merely semi-empirical and based on bearing capacity analyses (in general, without settlement evaluation). Fully instrumented pile load tests are very much informative for the elaboration of correlations between load-deformationbehaviour and in situ tests results, for establishing well-based design criteria. Athorough study was held in 2004 at the University of Porto, with the execution of anextensive site investigation and laboratory characterization tests, allowing good inputparameters for a pile prediction event. This project, supported by 4 constructioncompanies, made use of pile load tests, aiming to launch a class A prediction event, .e., all the predictions were submitted before the conduction of static pile load tests. Three different kinds of piles were executed: bored piles with temporary casing, continuous flight augered, CFA, piles with circular section - nominal diameter Ã¶600mm, and driven piles (square section, B=350mm). The piles were loaded axially to failure. The submitted predictions is resumed, revealing surprising overestimationsin the bored piles capacities, while for the driven piles there was an underestimationof the gains due to pile installation effects (densification, etc.). In this paper a simpleapproach to quantify the locked-in toe residual loads will be addressed. Copyright ASCE 2009.